2015
DOI: 10.23937/2474-3658/1510004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hospital Acquired Multidrug Resistant Organisms in a Tertiary Care Facility

Abstract: Background: Irrational use of antimicrobials and gaps in infection control practices have resulted in alarmingly high prevalence of multidrug resistant organisms (MDRO) globally. The objective of our study was to highlight the incidence of hospital acquired MDROs in our facility. Method:A retrospective analysis of surveillance data collected from January -December 2013 in a tertiary care hospital of Saudi Arabia. The Centre for Disease Prevention and Control (CDC) surveillance definitions were used, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…On the other hand, the results of the study showed that there were 12 antimicrobial-resistant (AMR) bacteria in 2016 and 12 AMR bacteria in 2017 as well. The majority of these isolates were gram-negative bacteria, which is consistent with the findings of another study carried out at a tertiary care facility in Riyadh where the gram-negative organisms were found to be the most common (82.2%) [ 6 ]. In agreement with these results, it was reported that high rates of resistance to commonly used antibiotics were from gram-negative bacteria [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, the results of the study showed that there were 12 antimicrobial-resistant (AMR) bacteria in 2016 and 12 AMR bacteria in 2017 as well. The majority of these isolates were gram-negative bacteria, which is consistent with the findings of another study carried out at a tertiary care facility in Riyadh where the gram-negative organisms were found to be the most common (82.2%) [ 6 ]. In agreement with these results, it was reported that high rates of resistance to commonly used antibiotics were from gram-negative bacteria [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
“…In a tertiary facility in Riyadh, it was found that “ A. baumannii isolates detected during the study period were almost resistant to all the drugs being tested. All the A. baumannii isolates would have been classified as XDR, i.e., resistant to three classes (all penicillin, cephalosporins, fluoroquinolones, and aminoglycosides) and carbapenems” [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…in this study. This is not an isolated phenomenon as evidenced in studies published from both high and low income countries (17,23,25,26) . Acinetobacter spp.…”
Section: Carbapenem Resistance Profile Was Analysed Between Isolates Of Ecoli Klebsiellamentioning
confidence: 85%
“…This could be because of increased selection pressure for microorganisms due to the use of multiple antibiotics in such a setting. Prevalence of MDRO's range from approximately 25% in studies from high income countries to 80% in that from low and middle income countries (11,17,18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation